PICTURES AS MEDIA IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOM TO IMPROVE STUDENTS’ SPEAKING SKILL - Eransya, Yona Pramela; Rochsantiningsih, Dewi; Haryati, Sri (Research and Development Journal of Education, 2025)
This is a case study research and examines the use of pictures as media to improve students’ speaking skill. This research limits the discussion by stating problem “What are the students’ perceptions toward the use of pictures in EFL classroom?” The aim of this research is to explain the students’ perceptions toward the use of pictures as media in EFL classroom. This research held in one of Vocational High School in Pemalang, Central Java, Indonesia. This research has three steps. The observation came first, the second step gave students questionnaires about pictures as media, and the last step gave interview to the students and English Teacher. The outcomes of this research is about pictures as media significantly useful to help students in EFL classroom especially to improve speaking skill. This is in line when the students agree that pictures help them increase their speaking skill in EFL class. The teacher also said the same thing about the pictures that it helps students in teaching and learning processes.